Multikinase Inhibition as a Therapeutic Strategy for Status Epilepticus: Current Evidence and Future Directions - Vaishnavi B.; Asha Nayak; Darshan Gowda L.M.; Sunil Kumar Kadiri (Current Signal Transduction Therapy, 2026)
Introduction:: Status epilepticus (SE) is a serious neurological emergency defined by prolonged or recurring seizures that frequently do not respond to standard antiepileptic medications. Recent revelations into the molecular underpinnings of SE, including neuroinflammation, oxidative stress, angiogenesis, and disruption of the blood-brain barrier, have stimulated research into targeted therapeutics. Lenvatinib, a multi-kinase inhibitor sanctioned for many cancers, has demonstrated potential neuroprotective and anti-inflammatory effects by targeting the VEGFR, FGFR, and PDGFR pathways, which are also involved in epileptogenesis. Methods:: This review examines the therapeutic potential of repurposing lenvatinib in the pilocarpine- induced status epilepticus model, a well-established preclinical framework that simulates human temporal lobe epilepsy. Preclinical evidence, mechanistic relevance, pharmacodynamics, blood-brain barrier permeability, and safety profiles were reviewed to determine the viability of lenvatinib as an adjunct or alternative therapy. Results:: Furthermore, the function of angiogenic signaling in the advancement of seizures and how lenvatinib's multitargeted mechanism may influence critical pathogenic pathways were also examined. Discussion:: Although existing evidence is insufficient, in silico and in vivo investigations indicate that lenvatinib may disrupt neuroinflammatory and vascular alterations essential to SE pathogenesis. Additional preclinical validation is necessary to verify its efficacy and safety. Conclusion:: This review seeks to establish a thorough basis for subsequent research on the repurposing of lenvatinib in neurotherapeutics.